2012
DOI: 10.1242/jcs.110494
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule guidance tested through controlled cell geometry

Abstract: SummaryIn moving cells dynamic microtubules (MTs) target and disassemble substrate adhesion sites (focal adhesions; FAs) in a process that enables the cell to detach from the substrate and propel itself forward. The short-range interactions between FAs and MT plus ends have been observed in several experimental systems, but the spatial overlap of these structures within the cell has precluded analysis of the putative long-range mechanisms by which MTs growing through the cell body reach FAs in the periphery of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 62 publications
3
34
0
Order By: Relevance
“…Indeed, MTs have been reported to be targeted to and captured at cellextracellular-matrix focal adhesions (Kaverina et al, 1998). MTs have been implicated in signaling, relaxation and trafficking at integrin-mediated adhesions, leading to destabilization of focal adhesions and an increased rate of turnover, a process that is essential for cell polarization and migration (Huda et al, 2012;Kaverina et al, 1998;Small and Kaverina, 2003;Stehbens and Wittmann, 2012). However, the relationship between cadherins and MTs is still unclear and controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, MTs have been reported to be targeted to and captured at cellextracellular-matrix focal adhesions (Kaverina et al, 1998). MTs have been implicated in signaling, relaxation and trafficking at integrin-mediated adhesions, leading to destabilization of focal adhesions and an increased rate of turnover, a process that is essential for cell polarization and migration (Huda et al, 2012;Kaverina et al, 1998;Small and Kaverina, 2003;Stehbens and Wittmann, 2012). However, the relationship between cadherins and MTs is still unclear and controversial.…”
Section: Introductionmentioning
confidence: 99%
“…The major obstacle to MT penetration into areas containing cadherin adhesions was not the reduction in the stability of plus ends and polymerization, but, instead, seemed to be the physical barrier formed by circular actin cables at the rear of the adhesion area. Indeed, in cells seeded on FN, it has been shown that MTs are guided along stress fibers to reach the leading edge (Huda et al, 2012). By contrast, cells on Ncad-Fc do not form longitudinal stress fibers but, instead, have actin filaments that are organized in a circular dense actomyosin belt.…”
Section: Discussionmentioning
confidence: 99%
“…[5153] In the context of cell motility, recent studies have shown that MTs not only play a role in the formation of lamellipodial protrusions at the front of a moving cell, [58] but are also important in the disassembly of focal adhesions (FAs) at the cell’s rear. [51,59,60] …”
Section: Key Cytoskeletal Events and Components Involved In Cell Mmentioning
confidence: 99%
“…In contrast, the rear of the cell is characterized by frequent MT catastrophes, induced by excess of active catastrophe-inducing factors, such as stathmin [61] and also by contact with focal adhesions. [62] MTs located there in are guided towards, [60] target focal adhesions [63] (with which cell attaches to the substrate, see Figure 5 and discussion in the next paragraph) and help to disassemble these multimolecular complexes [51] allowing the cell to retract its tail and ultimately move forward. For excellent discussion of asymmetric microtubule dynamics in migrating cells, the Reader is directed to review [74] .…”
Section: Key Cytoskeletal Events and Components Involved In Cell Mmentioning
confidence: 99%
See 1 more Smart Citation